2023
DOI: 10.3389/fimmu.2023.1150754
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade attenuates surgery-mediated immunosuppression and boosts Th1 immunity perioperatively in oesophagogastric junctional adenocarcinoma

Abstract: IntroductionThis timely study assesses the immunosuppressive effects of surgery on cytotoxic Th1-like immunity and investigates if immune checkpoint blockade (ICB) can boost Th1-like immunity in the perioperative window in upper gastrointestinal cancer (UGI) patients.MethodsPBMCs were isolated from 11 UGI patients undergoing tumour resection on post-operative days (POD) 0, 1, 7 and 42 and expanded ex vivo using anti-CD3/28 and IL-2 for 5 days in the absence/presence of nivolumab or ipilimumab. T cells were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Within the expanded lymphocyte population, there likely exists a mixed population of both pro-and anti-tumour T cells, and this is in keeping with our previous data [52]. Further studies will fully interrogate their specific immune phenotype and whether this can translate into an improvement in tumour control in murine models.…”
Section: Discussionsupporting
confidence: 83%
“…Within the expanded lymphocyte population, there likely exists a mixed population of both pro-and anti-tumour T cells, and this is in keeping with our previous data [52]. Further studies will fully interrogate their specific immune phenotype and whether this can translate into an improvement in tumour control in murine models.…”
Section: Discussionsupporting
confidence: 83%
“…Understandably, use of PD-1 blockade in the postoperative setting may help subvert the surgery-induced protumorigenic effect and propagate a stronger anti-tumor immune response enhancing immune surveillance and prolonging disease recurrence. A recent study (44) showed that the systemic effects of surgery decreased lymphocyte cytotoxicity and production of antitumor cytokines in PBMCs derived from OAC patients. The ability of OAC-derived lymphocytes to kill OE33 OAC cells in vitro was significantly decreased in PBMCs obtained 1 and 7 day postsurgery compared PBMCs obtained pre-operatively (on the day of surgery -day 0) or 6 weeks post-surgery.…”
Section: Recent Successes For Pd-1 Blockade In Oacmentioning
confidence: 99%